Efficacy and safety of insulin glargine/lixisenatide fixed‐ratio combination (iGlarLixi 1:1) in Japanese patients with type 2 diabetes mellitus inadequately controlled on oral antidiabetic drugs: A randomized, 26‐week, open‐label, multicentre study: The LixiLan JP‐O2 randomized clinical trial. (16th September 2020) - Terauchi, Yasuo; Nakama, Takahiro; Spranger, Robert; Amano, Atsushi; Inoue, Takahiro; Niemoeller, Elisabeth
Abstract: Aims: To assess efficacy and safety of 26‐week treatment with insulin glargine/lixisenatide fixed‐ratio combination (iGlarLixi) compared with insulin glargine U100 (iGlar) in Japanese patients with type 2 diabetes mellitus (T2DM) inadequately controlled on oral antidiabetic drugs (OADs). Materials and Methods: This phase 3, multicentre, open‐label, 1:1 randomized, parallel‐group study compared efficacy of iGlarLixi and iGlar in patients with T2DM, HbA1c of ≥7.5% to ≤9.5% and fasting plasma glucose ≤10.0 mmol/L (180 mg/dL). The primary endpoint was change in HbA1c from baseline to week 26. Results: Patients were randomized to iGlarLixi (n = 260) or iGlar (n = 261) (mean age 59.7 years, baseline BMI 26.04 kg/m 2, and HbA1c 8.04% [64.4 mmol/mol]). HbA1c reduction was significantly greater with iGlarLixi (−1.40% [−15.3 mmol/mol]) than with iGlar (−0.76% [−8.3 mmol/mol]). Significantly more iGlarLixi patients reached HbA1c <7% at week 26 (71.5% vs 38.5%, P  < .0001), with significantly lower weight gain (LS mean difference −1.06 kg, P  < .0001). Documented symptomatic hypoglycemia (plasma glucose ≤3.9 mmol/L [70 mg/dL]) was recorded in 14.2% of patients with iGlarLixi and 12.3% with iGlar. No severe hypoglycemia was reported in either group. Other than the expected gastrointestinal issues associated with glucagon‐like peptide 1 receptor agonists, we found no major difference in the incidence of TEAEs. Conclusions: HbA1c reduction was significantly greater with iGlarLixi than with iGlar; significantly more patients achieved HbA1c <7%, with no additional risk of hypoglycemia and without weight gain. iGlarLixi (1:1) provided an effective treatment option for Japanese patients with T2DM inadequately controlled on OADs. Clinical Trial Number: NCT02752828